Big Five personality and the psychedelic experience : An initial report - Kajonius, Petri J.; Sjöström, David ; 0000-0003-0004-1892; Claesdotter-Knutsson, Emma (Journal of Psychedelic Studies, 2025)
A surge in societal and scientific discussion surrounds psychedelic research. One surprising fact keeps standing out: Many users report the psychedelic experience as a positive and lasting impact on their quality of life. The present study aimed to explore the quality and consequences of the most impacting psychedelic experience, with the user's Big Five personality in focus. This experienced sample (N = 400) rated how challenging and mystical the experience was and the extent of positive and negative lasting life effects, together with the Big Five (IPIP-NEO-30). Interestingly, the results showed that most ranked it as among the most meaningful experiences in life, and that personality trait openness related to enhanced mystical and positive experiences, while neuroticism related to increased challenging and negative reports. We discuss limitations like the self-selected sample and the use of brief instruments. We conclude and recommend that individual differences in personality deserve continued consideration and should be measured and controlled for in future studies.
Publisher Copyright: © 2025 The Author(s). Open Access statement. This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (https://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted use, distribution, and reproduction in any medium for non-commercial purposes, provided the original author and source are credited, a link to the CC License is provided, and changes – if any – are indicated.
Keywords: Big Five; meaning; personality; psychedelics; quality of life